Only child [large type] - Navin, Rhiannon, 1978- (Thorndike Press, a part of Gale, a Cengage Company, 2018)
Squeezed into a coat closet with his classmates and teacher, first grader Zach Taylor hears shots ringing through the halls of his school as a gunman takes nineteen lives and irrevocably changes his community. While Zach's mother seeks justice by holding the shooter's parents responsible, Zach retreats into a world of books and art. Armed with newfound understanding, he sets out on a captivating journey towards healing and forgiveness, reminding us that sometimes the quietest voices speak the loudest.